Epidemiological investigation and drug resistance of Eimeria species in Korean chicken farms - Rochelle A. Flores; Binh T. Nguyen; Paula Leona T. Cammayo; Tuấn Cường Võ; Haung Naw; Suk Kim; Woo H. Kim; Byoung-Kuk Na; Wongi Min (BMC Veterinary Research, 2022)
Abstract Background Coccidiosis is a poultry disease that occurs worldwide and is caused by Eimeria species. The infection is associated with reduced feed efficiency, body weight gain, and egg production. This study aimed to investigate the current status of coccidiosis and anticoccidial resistance to anticoccidial drugs used as part of control strategies for this disease in Korean chicken farms. Results An overall prevalence of 75% (291/388) was found. Positive farms contained several Eimeria species (mean = 4.2). Of the positive samples, E. acervulina (98.6%), E. maxima (84.8%), and E. tenella (82.8%) were the most prevalent species. Compared with cage-fed chickens, broilers and native chickens reared in free-range management were more at risk of acquiring an Eimeria infection. Sensitivities to six anticoccidial drugs (clopidol, diclazuril, maduramycin, monensin, salinomycin, and toltrazuril) were tested using nine field samples. Compared with untreated healthy control chickens, the body weight gains of infected chickens and treated/infected chickens were significantly reduced in all groups. Fecal oocyst shedding was significantly reduced in four clopidol-treated/infected groups, three diclazuril-treated/infected groups, two toltrazuril-treated/infected groups, one monensin-treated/infected group, and one salinomycin-treated/infected group, compared with the respective untreated/infected control groups. Intestinal lesion scores were also reduced in three clopidol-treated/infected groups, one monensin-treated/infected group, and one toltrazuril-treated/infected group. However, an overall assessment using the anticoccidial index, percent optimum anticoccidial activity, relative oocyst production, and reduced lesion score index found that all field samples had strong resistance to all tested anticoccidial drugs. Conclusion The results of this large-scale epidemiological investigation and anticoccidial sensitivity testing showed a high prevalence of coccidiosis and the presence of severe drug resistant Eimeria species in the field. These findings will be useful for optimizing the control of coccidiosis in the poultry industry.